1983
DOI: 10.1099/0022-1317-64-10-2127
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Carboxypeptidase Involved in the Proteolytic Cleavage of the Influenza Haemagglutinin

Abstract: SUMMARYThe arginine carboxypeptidase involved in the proteolytic cleavage of the haemagglutinin of influenza A virus has been analysed by an assay employing a Sepharose-bound peptide containing radioactive arginine as a substrate. The enzyme activity has been extracted from purified virus with non-ionic detergents and has been separated from the haemagglutinin and from the neuraminidase by isoelectric focusing and by affinity chromatography. The carboxypeptidase present in virus grown in different host cells s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

1984
1984
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 38 publications
1
17
0
1
Order By: Relevance
“…In addition, the sequences downstream of this motif contain all of the information necessary for the maturation of a tachykinin peptide. The basic motif KKRKRR 136 provides a target for endoproteolytic cleavage by prohormone convertases (34) and subsequent trimming by carboxypeptidases (35). The glycine residue, Gly 130 , carboxyl-terminal to the tachykinin motif provides the NH 2 group for C-terminal amidation by peptidylglycine ␣-amidating mono-oxygenase (36).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the sequences downstream of this motif contain all of the information necessary for the maturation of a tachykinin peptide. The basic motif KKRKRR 136 provides a target for endoproteolytic cleavage by prohormone convertases (34) and subsequent trimming by carboxypeptidases (35). The glycine residue, Gly 130 , carboxyl-terminal to the tachykinin motif provides the NH 2 group for C-terminal amidation by peptidylglycine ␣-amidating mono-oxygenase (36).…”
Section: Resultsmentioning
confidence: 99%
“…Sturman & Holmes (1977) have shown that the MHV-A59 S polypeptide can be cleaved by trypsin and it appears likely that coronaviruses, in common with many enveloped RNA viruses, utilize a cellular trypsin-like endoprotease activity to achieve proteolytic processing. It is not yet known whether a second, carboxypeptidase, enzyme plays a role in the maturation of the coronavirus S protein, as has been shown for the influenza virus haemagglutinin (Garten & Klenk, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Only one nucleotide substitution could change the -R-S-S-Rmotif to -R-S-R-R-. it was (13)(14)(15)(16)(17)(18) suggested that H9N2 viruses isolates in Iran are potentially capable of becoming highly pathogenic. The presence of Serine amino acid has made it a crucial motif because only 1 nucleotide substitution (C to A or G) at two positions is enough to convert this motif to a virulent sequence.…”
Section: Discussionmentioning
confidence: 99%
“…In the course of the infection, HAO is cleaved into two disulfidelinked polypeptide chains, HAl and HA2 (13). The cleavage site of 13 from 15 HA subtypes (all HA subtypes except H5 and H7) consist of four amino acids including a single arginine residue which is removed from the COOH terminus of the HAl after cleavage by means of virus-associated carboxypeptidase (14). A correlation between cleavability of the HAO and pathogenicity has been established.…”
Section: Introductionmentioning
confidence: 99%